Success Comes in Waves: The role of neuronal oscillations in the modulation of visuospatial attention, perception and cortical excitability - Nannetti, Francesca/FMN (2025)
The overall aim of this thesis is to contribute to investigations into the role that neuronal oscillations play in the top-down control of visuospatial attention, perception and more generally, cortical excitability. In the achievement of this, a range of studies have been conducted, attempting to both replicate current findings within the literature, as well as contribute new knowledge through the implementation of carefully designed studies. Open-science methods have also been adopted within this thesis, where secondary data has been utilised to conduct novel analyses that offer new insights into existing research findings. Prior to examining these though, it is first critical that several topics are outlined and explored so that a comprehensive understanding of the relevant background can be achieved; creating an important foundation of knowledge that the progression of this thesis relies upon. This general introduction chapter will aim to provide this, with an overview of neuronal oscillations, covering the history of their initial discovery to their use as an informative neural signal in modern research. It will then proceed to highlight important neuroimaging techniques that are cited in subsequent chapters, where all have been applied in the experimental studies that make up this thesis, to record or induce oscillations within the cortex.